Factors Affecting Fashion Education Students’ Entrepreneurial Interest in Fashion Brand Development - Riska Widiya Ningsih; Rina Rachmawati (Universitas Negeri Semarang, 2026)
Entrepreneurial interest in developing a fashion brand represents a crucial competency for Fashion Design students in responding to the increasing competitiveness of the fashion industry. Such interest is shaped by multiple factors related to students’ attitudes, experiences, and entrepreneurial readiness. This study aims to examine the factors influencing fashion education students’ entrepreneurial interest in fashion brand development. A quantitative approach with a descriptive research design was employed. The population consisted of Fashion Design Education students at Universitas Negeri Semarang, with a sample of 50 students selected for analysis. Data were collected using a structured questionnaire based on a Likert scale. The collected data were analysed using descriptive statistics and simple linear regression with the assistance of IBM SPSS Statistics 26. The findings indicate that the influencing factors were categorized as high, with a mean score of 78.48 (SD = 7.285). Students’ entrepreneurial interest in developing fashion brands was also high, with a mean of 78.30 (SD = 9.702). These results suggest that students demonstrate strong interest, motivation, and readiness to establish independent fashion brands. Instrument validity and reliability testing confirmed high internal consistency, indicating that the data were suitable for further statistical analysis.